Seismic Resistance of Reinforced Concrete Building Frames Based on Interval Assessment of the Coefficient of Permissible Damage - Ashot Tamrazyan; Tatiana Matseevich (Buildings)
The main method for assessing the seismic resistance of buildings in the standards of most countries is the linear-spectral method. This method allows for the calculation of the spatial model of a building for seismic load in the elastic range without resorting to direct integration of the equations of motion. Nonlinear characteristics of reinforced concrete structure materials are usually considered integrally using the reduction factor. However, the values of this factor in the Russian standards are not sufficiently substantiated, as the later studies show. To determine the coefficient of permissible damage (reduction factor), six reinforced concrete frames were considered, with different parameters such as span length, number of spans, and number of floors. The design parameters of beams and columns (section sizes, reinforcement, etc.) were preliminarily selected based on the calculation using the linear-spectral method. In the second stage, numerical modeling was carried out in the OpenSEES PC to implement the pushover analysis procedure. Then, the coefficient of permissible damage was estimated by processing the capacity curves obtained on the basis of nonlinear static calculation. The value of the sought coefficients is practically not affected by the number of stores of the frame; however, with an increase in the number of spans, the coefficient K1 increases, which is explained by a decrease in the plasticity of the system. On average, for the frames under consideration, the coefficient K1 was 0.526, which is 1.5 times greater than the coefficient proposed in modern Russian standards, K1 = 0.35. The results obtained on the basis of pushover analysis are compared with the coefficients K1 determined through the values of the average degree of damage (d) of the buildings according to the modified seismic scale MMSK-86. For various types of reinforced concrete frame buildings, K1 = 0.51 was obtained. It is recommended that the coefficient K1 for reinforced concrete frame buildings should be increased to a value of at least K1 = 0.5 in the Russian standard.